Criteria inadequacy of the vehicles used for the calculation of safety parameters in the EN1317-TB11 test - Özcanan, Sedat; Özcan, Özgür (SAGE PUBLICATIONS LTD, 2022)
Road restraint systems-RRS are passive safety designs installed on roadsides to ensure the safety of errant vehicle passengers as well as pedestrians. The adequacy of these systems is assessed through full-scale vehicle crash testing for which evaluation criteria are determined by standards such as EN1317. Recently the same RRS is crash tested two times with two different 900 kg passenger cars and test results varied significantly. After a failed crash test instead of modifying the barrier test vehicle was replaced and the same test was repeated. It was surprising to see that the failed RRS this time satisfied the EN1317 evaluation criteria. Despite the use of the same mass vehicle in the crash tests, the different results obtained were a source of motivation for investigating the inadequacy of EN1317. In this study, the adequacy of the 900 kg vehicle criteria used in the determination of the safety parameters in the EN1317-TB11 test was investigated by creating validated finite element-FE models. After the FE analysis it was concluded that test vehicle properties, such as vehicle mass and velocity provided in EN1317 are deemed to be insufficient and more explicit vehicle selection parameters, given in the study, are needed to provide safer and more uniform crash testing results.
Keywords: Safety analysis; crash testing; road restraint systems; ASI-THIV; EN 1317 standard